5x(x的平方-2x-4)+x的平方(x-1)
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/03 13:36:01
5x(x的平方-2x-4)+x的平方(x-1)5x(x的平方-2x-4)+x的平方(x-1)5x(x的平方-2x-4)+x的平方(x-1)5x(x²-2x-4)+x²(x-1)=5
5x(x的平方-2x-4)+x的平方(x-1)
5x(x的平方-2x-4)+x的平方(x-1)
5x(x的平方-2x-4)+x的平方(x-1)
5x(x²-2x-4)+x²(x-1)
=5x³-10x²-20x+x³-x²
=6x³-11x²-20x
=x(6x²-11x-20)
原式=5x^2-10x-20+x^3-x^2
=x^3+4x^2-10x-20
一步一步算
2x平方-5x+x的平方+4x-3x的平方-2
[(x+2)/(x+3)-(x+1)/(x+2)+(x+4)/(x+5)-(x+3)/(x+4)]/[(x的平方+7x+13)/(x的平方+8x+15)]
(x的平方-5x+4)的平方+x的平方-5x-2因式分解
5x+x的平方-4x+2-7x的平方,其中x=5
5x(x的平方-2x-4)+x的平方(x-1)
3x的平方-2x-(-4x的平方+3x-2) 3(x的平方-5x)-3(2x的平方-4x-1)
(x-1分之x的平方+5x)-(x的平方-x的平方-x分之2x的平方+4x)
(X+2)/(X的平方-2X)-(X-1)/(X的平方-4X+4) 化简
x(x的平方-2x+1)-3x(x的平方-4x+1)
2/x-x的平方-1/x的平方-x
(3x平方-x-2)平方=(2x平方+4x-8)平方-(x的平方-5x+6)平方 解方程
(3x平方-x-2)平方=(2x平方+4x-8)平方-(x的平方-5x+6)平方 解方程
(4x+20)(x的平方-6x+9)/(3x-x的平方)(x的平方+2x-15)
(x+2)(x的平方-2x+4)+(x-5)(x+5x^2+25)化简
x的平方+x+2
2x的立方+x的平方-5x-4
先化简,再求值:4x的平方-{-3x的平方-[5x-x的平方-(2x的平方-x)]+4x}
5x的平方+4-3x的平方-5x-2x的平方-5+6x 化简~